Pengalaman Siswa Kelas V Sekolah Dasar dalam Menggunakan Teknik Draw and Tell untuk Memahami Isi Bacaan - Anggraeni, Silvia; Muh Arafik; Ardika Rahma Kumalasari; Etyka Rina Mahanani; Muhammad Firdaus Mashuri; Richa Okta Barera; Weinty Anggraini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study is to describe how fifth-grade elementary school students use the Draw and Tell method to understand texts. This study employs a qualitative approach with a phenomenological orientation. The research subjects consisted of fifth-grade elementary school students who were learning to read using the Draw and Tell method. Data collection techniques included observation, interviews, questionnaires, and documentation. Data analysis was conducted through data reduction, data analysis, and conclusion analysis. The findings indicate that the “Draw and Tell” method provides a positive learning experience for students. Students became more attentive and enthusiastic about learning to read because reading activities involved drawing and retelling the text. These activities helped students understand the characters, plot, and content of the stories more easily. Additionally, the use of drawings boosted students’ self-confidence when they returned to the classroom. Furthermore, the “Draw and Tell” technique made the learning process more active, engaging, and less tedious. However, some students still struggled to draw illustrations that matched the story’s content and felt uncomfortable when asked to do so in class. Based on the findings of this study, it can be concluded that the “Draw and Tell” technique can help students understand reading concepts through simultaneous visual and verbal activities. This technique is also effective in creating a meaningful learning environment and increasing engagement.